Research and conditions of JSCB supercapacitors electric power supply system - Сліпченко, Микола Іванович; Письменецький, Віктор Олександрович; Гуртовий, Михайло Юрійович (Eastern-European Journal of Enterprise Technologies, 2012)
The results of investigations of the main characteristics of the traction system of the electric motorcar (EM) with application of supercapacitors (SC) at the stage of EM starting, acceleration and subsequent accumulator battery (AB) energy supply are given